Nontraumatic Tibial Polyethylene Insert Cone Fracture in Rotating-Platform Total Knee Arthroplasty - Cillian J. Keogh, BSc, BMBS, MCh, MRCSI (Arthroplasty Today, 2021)
We report a case of a fracture through the polyethylene (PE) insert cone in a rotating-platform (RP) primary total knee arthroplasty (TKA) implant. This is the first reported case of cone fracture with this particular implant. This case highlights a 65-year-old female presenting with a 4-month history of knee pain and symptoms of instability 10 years after primary RP TKA. At the time of revision surgery, the PE insert cone was found to be fractured 10 mm from the inferior surface of the PE liner. Analysis suggests that the cone fracture occurred by fatigue failure which caused loosening of the tibial tray. Clinicians should be aware that this is a potential cause of failure with an RP TKA in the setting of symptoms including instability and pain.